2022
DOI: 10.1007/s10533-022-00913-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of riverine dissolved organic matter using a complementary suite of chromatographic and mass spectrometric methods

Abstract: Dissolved organic matter (DOM) plays a fundamental role in nutrient cycling dynamics in riverine systems. Recent research has confirmed that the concentration of riverine DOM is not the only factor regulating its functional significance; the need to define the chemical composition of DOM is a priority. Past studies of riverine DOM rested on bulk quantification, however technological advancements have meant there has been a shift towards analytical methods which allow the characterisation of DOM either at compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 120 publications
(133 reference statements)
0
3
0
Order By: Relevance
“…Raeke et al also reported that very polar compounds were poorly extracted by SPE during DOM analysis but these compounds also showed low MS signal responses . Overall, no analytical method is capable of achieving comprehensive characterization of DOM . The analytical window of HRMS for DOM is jointly influenced by the selectivity of SPE, LC retention, ionization source, and MS detectors, among others. …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raeke et al also reported that very polar compounds were poorly extracted by SPE during DOM analysis but these compounds also showed low MS signal responses . Overall, no analytical method is capable of achieving comprehensive characterization of DOM . The analytical window of HRMS for DOM is jointly influenced by the selectivity of SPE, LC retention, ionization source, and MS detectors, among others. …”
Section: Results and Discussionmentioning
confidence: 99%
“…55 Overall, no analytical method is capable of achieving comprehensive characterization of DOM. 56 The analytical window of HRMS for DOM is jointly influenced by the selectivity of SPE, LC retention, ionization source, and MS detectors, among others. 57−59 We further evaluated the reproducibility of the developed method in terms of elution profile, mass peak detection, and mass peak intensity 41,60,61 since good reproducibility is the basis for reliable and semiquantitative analysis of MS data.…”
Section: Analysis Of Original Dom By Online Spe-lc-qtof Msmentioning
confidence: 99%
“…Such elevated nutrient concentrations are commonly observed in UK agricultural catchments (Yates et al 2019a). Contradictory observations from Graeber et al (2012) and others (Sachse et al 2005) suggest catchments with a high proportion of agricultural activity export structurally complex DOM, characterised by elevated DOC concentrations and a dominance of humic-like fluorescent DOM, though other studies (Lloyd et al 2021;Mena-Rivera et al 2021) indicate DOM in agricultural catchments has a high proportion of lower molecular weight compounds resulting from microbial processing of terrestrially derived DOM. Similarly, both Yates et al (2019a) and Williamson et al (2021) in a pan-UK study concluded that higher DOC, higher Specific UV Absorbance (SUVA) and higher DOC:DOC ratios were consistently observed in peaty catchments than in lowland intensively farmed agricultural catchments.…”
Section: Introductionmentioning
confidence: 99%